2001
DOI: 10.1111/j.1574-6968.2001.tb10632.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesophilic cyanobacteria producing thermophilic restriction endonucleases

Abstract: When searching for the site-specific endonucleases in several strains of Phormidium we made the following observations. Among the 16 strains that originated from 15 species of Phormidium, 12 produced one or more restriction enzymes, of which two produced the highly thermophilic restriction endonucleases PtaI and PpaAII with their optimum activity at 65-80 degrees C, which is far above the lethal temperature for the host microorganism (40 degrees C). These two temperature-resistant enzymes are isoschizomers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…In Mycobacterium tuberculosis and E. coli , mutations in the rpoB gene can confer resistance to the antibiotic rifampicin (Telenti et al ., ; Rodriguez‐Verdugo et al ., ; Hammerling et al ., ). Additionally, HGT may result in a change in growth optima along an already acquired trait axis (Piechula et al ., ). For example, a study of Bacillus subtilis isolated from soil communities showed that the addition of maltose genes by HGT to a specific sub‐taxa resulted in higher growth on that substrate when compared with other closely related sub‐taxa and, thus, Maestro rather than Renaissance trait differentiation.…”
Section: Evolutionary Models Of Microdiversitymentioning
confidence: 97%
“…In Mycobacterium tuberculosis and E. coli , mutations in the rpoB gene can confer resistance to the antibiotic rifampicin (Telenti et al ., ; Rodriguez‐Verdugo et al ., ; Hammerling et al ., ). Additionally, HGT may result in a change in growth optima along an already acquired trait axis (Piechula et al ., ). For example, a study of Bacillus subtilis isolated from soil communities showed that the addition of maltose genes by HGT to a specific sub‐taxa resulted in higher growth on that substrate when compared with other closely related sub‐taxa and, thus, Maestro rather than Renaissance trait differentiation.…”
Section: Evolutionary Models Of Microdiversitymentioning
confidence: 97%
“…2004). Piechula et al. (2001) demonstrated that some cyanobacteria can produce thermostable enzymes.…”
Section: Cyanobacterial Bioactive Compoundsmentioning
confidence: 99%
“…As was suggested by several authors (De Waard and Duyvesteyn 1980; Janulaitis et al. 1988; Piechula et al. 2001), presence or absence of restriction endonucleases might be helpful in distinguishing strains of the same species or subspecies.…”
Section: Discussionmentioning
confidence: 86%
“…After 24 h of incubation in 1.0 l Luria Broth at 25°C, cultures of P. carotovorum were harvested by centrifugation, washed in buffer (10 mmol l −1 Tris–HCl, 25 mmol l −1 KCl, pH 6·8), suspended in 3·0 ml sonication buffer (10 mmol l −1 Tris–HCl, 50 mmol l −1 KCl, pH 6·8) and kept frozen until the analysis for the presence of restriction endonucleases was performed. The restriction enzymes were isolated as described earlier (Piechula et al. 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation